Single-Cell Transcriptomics Reveals Spatial and Temporal Turnover of Keratinocyte Differentiation Regulators - Finnegan, Alex; Cho, Raymond J.; Luu, Alan; Harirchian, Paymann; Lee, Jerry; Cheng, Jeffrey B.; Song, Jun S. (Frontiers in Genetics, 2019)
Keratinocyte differentiation requires intricately coordinated spatiotemporal expression changes that specify epidermis structure and function. This paper utilizes single-cell RNA-seq data from 22,338 human foreskin keratinocytes to reconstruct the transcriptional regulation of skin development and homeostasis genes, organizing them by differentiation stage and also into transcription factor (TF)-associated modules. We identify groups of TFs characterized by coordinate expression changes during progression from the undifferentiated basal to the differentiated state and show that these TFs also have concordant differential predicted binding enrichment in the super-enhancers previously reported to turn over between the two states. The identified TFs form a core subset of the regulators controlling gene modules essential for basal and differentiated keratinocyte functions, supporting their nomination as master coordinators of keratinocyte differentiation. Experimental depletion of the TFs ZBED2 and ETV4, both predicted to promote the basal state, induces differentiation. Furthermore, our single-cell RNA expression analysis reveals preferential expression of antioxidant genes in the basal state, suggesting keratinocytes actively suppress reactive oxygen species to maintain the undifferentiated state. Overall, our work demonstrates diverse computational methods to advance our understanding of dynamic gene regulation in development.